Crossed Aphasia. II: Why Are Deep Lesions Overrepresented with Respect to Standard Aphasia? - M. Laiacona; E. Capitani; C. Stangalino; L. Lorenzi (Behavioural Neurology)
In this paper we have reviewed the cases of vascular crossed aphasia reported in the literature, in order to check whether deep lesions are really overrepresented in crossed aphasia with respect to standard aphasia. The comparison with a large sample of standard left-hemisphere-damaged aphasics revealed a significantly higher incidence of purely deep lesions in crossed aphasics than in standard aphasics. The overrepresentation of deep lesions in crossed aphasia appears to be contingent on the co-occurrence of aphasia and Unilateral Neglect after right-hemisphere lesion. This suggests an interaction between language and attentional mechanisms in the case of reversed language lateralisation: the overcrowding of these functions in the right hemisphere could make language more vulnerable after right deep lesions.